EFFECT OF AWARENESS ON KNOWLEDGE OF NON-ALCOHOLIC FATTY LIVER DISEASE AMONG NON-GI PHYSICIANS - Adil, Noreen; Mehraj, Adil; Gilani, Mehwish; Akram, Ammad (Journal of Ayub Medical College Abbottabad, 2025)
Objective: To measure the base line level of knowledge among non-gastroenterology physicians and compare knowledge after sharing of reading material about NAFLD upon reassessment. Study design: Quasi-experimental. Place and duration of study: POF Hospital Wah Cantt Methodology: Proforma containing various NAFLD related questions covering three domains including risk factors, diagnostics and treatment were included. The Proformas were handed over to all participants involved in the study. The first part of the questionnaire comprised demographic information of the participants. The second part of the questionnaire was about the knowledge of the doctors regarding NAFLD. The questionnaire comprised of 12 questions including multiple choice questions & questions with yes or no with a total 25 parameters. The maximum achievable score was 25. The primary outcome was the frequency of distinct categories of score before and after creating awareness. Results: Nine non-gastroenterology (22.5%) physicians had good knowledge, 17(42.5%) had fair knowledge and 12(30.0%) had poor knowledge. After the awareness campaign, 10(25.0%) participants had excellent knowledge, 9(22.0%) had very good knowledge, 18(45.0) had fair knowledge and only one participant (2.5%) had poor knowledge with p value less than 0.05. Conclusion: We concluded that primary care physicians underestimate the frequency of NAFLD and fail to recognize its risk factors, diagnostics and treatment. The adequate use of awareness campaigns improved their knowledge effectively. Keywords: Awareness, Liver, Non-alcoholic fatty liver disease (NAFLD), prevalence